EMPATI DAN HOMOFILI DALAM KOMUNIKASI POLITIK PEMENANGAN PEMILIHAN LEGISLATIF - Choirul Muna; Guntur Freddy Prisanto; Niken Febrina Ernungtyas; Irwansyah Irwansyah; Sekartaji Anisa Putri (Scriptura, 2020)
Empathy and homophily communication in campaigns is important to garner public support in the era of democracy. Loyal community support can be achieved if political actors make empathy and homophile communication appropriately. This study aims to find out how empathy and homophile communication carried out by Gus, a legislative candidate, is able to win votes from a community that is basically apathetic to politics, namely the thoriqoh congregation. The research method used is a qualitative approach, with in-depth interview and observation data collection techniques. The results showed that the communication of empathy and homophilia carried out by Gus, made it seen as part of the Thoriqoh congregation itself thus increasing its credibility. The homophile aspect fulfilled by Gus so that he gets full loyal support from the Thoriqoh congregation is in terms of equality in dressing, religion, speaking, behaving, and in carrying out rituals.